Pengaruh Efektivitas Program Pelatihan Divisional dan Implementasi Penghargaan yang Adil Terhadap Kinerja Karyawan PT. Mentari Trans Nusantara - Yulia Riani; Ana Ramadhayanti (Indo Publishing, 2025)
In industrial competition, HR development is an important part of achieving Company goals. Two aspects of HR development that affect employee performance are divisional training programs and fair reward implementation. This study aims to analyze the effect of divisional training program effectiveness and fair reward implementation on employee performance at PT. Mentari Trans Nusantara. This study uses a quantitative approach with a questionnaire to 48 respondents who have participated in training and received awards. Data analysis techniques use validity, reliability, multiple linear regression, T-test, F-test, and coefficient of determination with the help of SPSS 27 software. The results of the study showed that divisional training had a positive and significant effect on employee performance with a regression coefficient value of 0.422. In addition, fair rewards also showed a positive and significant effect on employee performance with a coefficient value of 0.382. Simultaneously, the two variables were able to explain 55.5% of the variation in employee performance improvement. These findings indicate that the combination of divisional training and fair rewards is an effective strategy in improving HR performance. This study is expected to be a reference in formulating employee development policies that are oriented towards results